Tongue-coating and mixed saliva obtained from smokers and/or drinkers: nitric oxide/nitrite contents - Souza, Marise Ramos de; Genestra, Marcelo (Cadernos UniFOA, 2017)
The aim of this study was to investigate comparatively the concentration of a nitrogen radical, particularly nitric oxide (NO)/nitrite (NO2 -), in the tongue-coating and mixed saliva obtained from smokers/non-smokers and drinkers/non-drinkers, proving the cytotoxic and cytoprotective effect of these free radicals in oral metabolism and physiophatolology of oral diseases. Masticatory (stimulated) methods were used in order to determine the salivary flow rates of 100 patients. The tongue-coating was obtained through of tongue cleaning named Kolbe’s cleaner. Nitrite contents was measured spectophotometricaly by Griess method. Despite the NO been admittedly an important mediator of some physiological functions, when it is generated in excess it acts as the molecule-key of the cellular damage and tissue injury. The results point out that the association tobacco/alcohol points positive correlation between the increasing concentration of nitrogen radicals in the mixed saliva in order to favour tobacco/alcohol users, in comparison with the control group (not smokers/not drinkers). However, the NO/NO2 - concentration in tongue-coating is worthless, comparing to mixed saliva.